IMPLEMENTATION OF THE PRINCIPLES OF DIVERSITY AS REINFORCING RELIGIOUS MODERATION: STUDY OF SURAH AL-HUJURAT VERSE 13 - Nasrulloh, Lalu; Yusviranty2, Rara Dwi; Fatimah, Ariyani (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
The research with the title Implementation of the Principles of Diversity as Reinforcing Religious Moderation: Study of Surah Al-Hujurat verse 13 is qualitative research with an analytical descriptive approach. The focus of the study is the principle of diversity as a reinforcement of religious moderation, the study of Surah Al-Hujurat verse 13. The purpose of this study is to describe and explain the form and implementation of the principle of diversity as a reinforcement of religious moderation. The results of this study found four forms of implementation of the principle of diversity which are believed to be used as reinforcement for religious moderation in Indonesia, namely Bhinneka Tunggal Ika, nationalism, responsible freedom, and insight into the archipelago.